STRATEGI PENGEMBANGAN KELEMBAGAAN KELOMPOK TANI JAGUNG DI KECAMATAN ANTINGGOLA KABUPATEN GORONTALO UTARA - Amin, Nur Silfiah; Halid, Amir; Indriani, Ria; Tangahu, Rivan (Agrinesia: Jurnal Ilmiah Agribisnis, 2024)
Nur Silfiah Amin. Institutional Development Strategy of Maize Farmers Group in Atinggola District North Gorontalo Regency. The research aims to analyze alternative institutional development strategies for corn farmers in Atinggola sub-district, North Gorontalo district. This research was conducted in Atinggola subdistrict, survey research method using probabaility sampling technique totaling 24 samples. Date analysis using SWOT analysis. Based on the results of SWOT testing, it can be seen that IFAS 1,47 and EFAS 1,79 are in quadrant I, which supports an aggressive strstegy or SO (Stenhgts-Opportunities) strategy. This indicates the existence of strengths and opportunities in strategies that can be applied in the research area to develop farmer group institutions, meaning that the alternatives carried out by farmer groups optimize to avpid weaknessees and threats there.